Intrinsically Unstructured Carboxy Terminus of Bacillus Lipase is Essential for its Function - Khurana, Jyoti; Manisha; Singh, Ranvir; Kaur, Jagdeep (Protein and Peptide Letters, 2014)
We have identified intrinsically unstructured C-terminus of a Bacillus lipase. In an effort to understand the possible role of this C-terminus unstructured region, 10, 20 and 30 amino acids were serially deleted from C-terminal region of the lipase. The catalytic properties of wild type and resulted truncated enzymes were compared. Deletion of 10 amino acids from C-terminus region resulted in decrease in transcription of lipase, specific enzyme activity and extracellular secretion of lipase in comparison to wild type while no effect on lipase aggregation was observed. Negligible activity was observed upon deletion of 20 amino acids. The homology model of the protein demonstrated that the tertiary structure of the protein was held together by these C-terminus residues due to six critically placed hydrogen bonds. Therefore Cterminus was essential for the tertiary structure and enzyme activity of lipase. Due to structural flexibility and plasticity originating from the lack of a definite-ordered 3D structure, such disordered regions might represent a major functional advantage for proteins.
Keywords: Aggregation